Angular dependent torque measurements on CaFe0.88Co0.12AsF. (24th June 2016) - Xiao, H; Gao, B; Ma, Y H; Li, X J; Mu, G; Hu, T
Abstract: Out-of-plane angular dependent torque measurements were performed on CaFe0.88 Co0.12 AsF (Ca1 1 1 1) single crystals. In the normal state, the torque data shows sin ⁡ 2 θ angular dependence and H 2 magnetic field dependence, as a result of paramagnetism. In the mixed state, the torque signal is a combination of the vortex torque and paramagnetic torque, and the former allows the determination of the anisotropy parameter γ . At T = 11.5 K, γ (11.5 K ≃ 0.5 T c ) = 19.1, which is similar to the result of SmFeAsO0.8 F0.2, γ ≃ 23 at T ≃ 0.4 T c . So the 11 1 1 is more anisotropic compared to 11 and 122 families of iron-based superconductors. This may suggest that the electronic coupling between layers in 1 1 1 1 is less effective than in 11 and 122 families.